Gaining Knowledge about Resilient Therapy: How Can It Support Kinship Carers?. (8th October 2016) - Hill, Lindsay; Hart, Angie
Abstract: The research reported on here examined the utility of a multidimensional model for operationalising the findings from a research-informed approach known as Resilient Therapy (RT). The approach is designed to support practitioners, carers, parents and young people in contexts of multiple disadvantages. Seven kinship carers and six children were involved in collaborative action research. Kinship carers met together, on eighteen occasions over a period of fifteen months, to learn about RT and explore how they might draw on the approach to inform their care of children. Children were interviewed on two occasions. Learning arising from the research suggests the importance of introducing RT as a collaborative model that builds opportunities for reflection and action. Carers are supported to find their own solutions, based on an understanding of their relationships with children, children's relationships with them and with others in their network. It is an approach which is attentive to what families do and views family practices as emerging in complex ecological systems. The study is located in an inequalities-informed conceptualisation of resilience research. Findings reinforce the importance of understanding resilience building as a process which parents/carers/practitioners and young people can facilitate, but also one that must be attentive to the socio-economic systems around families.